A bibliometric analysis of the scientific literature on Fairtrade labelling. (3rd December 2018) - Ruggeri, Giordano; Orsi, Luigi; Corsi, Stefano
Abstract: Since its foundation, the Fairtrade movement has attracted the attention of consumers, practitioners, media and scholars. Discussing the role that Fairtrade can play on a global yet locally rooted scale is very complex, as research reports contrasting results about its usefulness and effectiveness. This study examines scientific research on Fairtrade over the last decades by conducting a bibliometric analysis of the literature published on the ISI Web of Knowledge Core Collection, which included 876 papers by 1, 293 authors in 432 journals. Results show that despite this being a relatively recent field of study, Fairtrade has been approached from different disciplines with different methodologies and objectives. The structured quantitative study of the literature enabled us to inspect how research has evolved over the years in the light of the changes faced by Fairtrade, to explore its scope in the broader field of the global market, to detect current research schools and perspectives within the network and to identify hitherto unaddressed issues and unconnected subfields.